RNF146 Inhibits Excessive Autophagy by Modulating the Wnt-β-Catenin Pathway in Glutamate Excitotoxicity Injury - Yang, Yuefan; Luo, Peng; Xu, Haoxiang; Dai, Shuhui; Rao, Wei; Peng, Cheng; Ma, Wenke; Wang, Jiu; Xu, Hongyu; Zhang, Lei; Zhang, Sai; Fei, Zhou (Frontiers in Cellular Neuroscience, 2017)
Glutamate induced excitotoxicity is common in diverse neurological disorders. RNF146 as an E3 ubiquitin ligase protects neurons against excitotoxicity via interfering with PAR polymer-induced cell death (parthanatos). However, the neuroprotective role of RNF146 has not been fully understood. We aimed to investigate the role of RNF146 in modulating autophagy in HT22 cells under glutamate excitotoxicity injury. Here we found that induction of RNF146 decreased the cellular damage and excitotoxicity induced by glutamate. RNF146 also suppressed the excessive autophagy, which is detrimental to HT22 cells survival, induced by glutamate or rapamycin treatment. In addition, we find that Wnt/β-catenin was a negative regulation factor for autophagy in glutamate excitotoxicity. Over-expression of RNF146 promoted Wnt/β-catenin signaling, which was related to destabilization of β-catenin destruction complex. These results indicated that RNF146 acted as a neuroprotective agent against glutamate-induced excitatory damage, and this neuroprotection might be at least partly dependent on the inhibition of excessive autophagy by regulating Wnt/β-catenin signaling.